Warm Climate Production Guidelines for Hardy Hibiscus - Rick Schoellhorn; Alexis A. Richardson (EDIS)
This document is ENH 994, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 11, 2004.